Promoting EF With Preschool Interventions: Lessons Learned From 15 Years of Conducting Large-Scale Studies - Mattera, Shira; Rojas, Natalia M.; Morris, Pamela A.; Bierman, Karen (Frontiers in Psychology, 2021)
In the past two decades, a growing number of early childhood interventions have targeted children’s executive function (EF), building on the theory that promoting EF skills in preschool may play a key role in reducing the substantial gaps in school readiness and later achievement based on income. Despite the expansion of EF-focused interventions across preschool, research evidence is mixed regarding what works to promote EF development and the impact of these interventions on children’s EF skills, and subsequently, their academic and behavioral outcomes. This paper reviews four approaches for improving children’s EF skills: (a) changing behaviors, (b) improving social-emotional learning, (c) promoting play and direct training of EF skills, and (d) improving cognitive skills. We describe program effects from rigorous trials testing these approaches, including summarizing the findings from four large-scale intervention research studies conducted by the authors, involving over 5000 children. We conclude by exploring open questions for the field and future directions for research and intervention program development and refinement.